1993
DOI: 10.1083/jcb.121.3.599
|View full text |Cite
|
Sign up to set email alerts
|

The Ca(2+)-binding domains in non-muscle type alpha-actinin: biochemical and genetic analysis.

Abstract: Abstract. Dictyostelium c~-actinin is a Ca:+-regulated F-actin cross-linking protein. To test the inhibitory function of the two EF hands, point mutations were introduced into either one or both Ca2+-binding sites. After mutations, the two EF hands were distinguishable with respect to their regulatory activities. Inactivation of EF hand I abolished completely the F-actin cross-linking activity of Dictyostelium discoideum o~-actinin but Ca 2+ binding by EF hand H was still observed in a *sCa 2+ overlay assay. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 56 publications
1
73
0
Order By: Relevance
“…This regulation is mediated by two perfect EF-hand regions in the C-terminus of the subunits [4,11]. The concentrations of the small acidic Ca2+.binding proteins c, almodulin [12] and calfumirin [13] are also essentially unaltered during growth and development.…”
Section: Lntroductlunmentioning
confidence: 99%
See 1 more Smart Citation
“…This regulation is mediated by two perfect EF-hand regions in the C-terminus of the subunits [4,11]. The concentrations of the small acidic Ca2+.binding proteins c, almodulin [12] and calfumirin [13] are also essentially unaltered during growth and development.…”
Section: Lntroductlunmentioning
confidence: 99%
“…Many of the effects of Ca 2+ are exerted via proteins containing EF-hand domains for Ca 2+ binding as a common structural motif [I,2], Proteins like a-actinin or spectrin harbor intramolecular EF-regions as regulatory domains [3,4], others act either as monomeric proteins (e.g. calmodulin, SI00) that transiently interact with their targets or as permanently bound regulatory subunits [5][6][7].…”
Section: Lntroductlunmentioning
confidence: 99%
“…Binding of calcium to the EF-hands might therefore regulate binding to F-actin. This could explain the regulation of actin binding by calcium in several non-muscle a-actinins Witke et al, 1993).…”
mentioning
confidence: 99%
“…Calcium binding to the EF hand modules in ␣-actinin decreases the interaction between ␣-actinin and actin (26,27). Fukami et al (28,29) have shown that the skeletal muscle isoform of ␣-actinin binds phosphatidylinositol 4,5-bisphosphate and that the actin gelating activity of the protein was enhanced by the phospholipid.…”
mentioning
confidence: 99%